Rancang Bangun Aplikasi Pengelolaan Aset Elektronik Berbasis Website Pada RSUD Dr Soetomo Surabaya - Rachmansyah Anessa Putra; Endra Rahmawati; Norma Ningsih (Jurnal Sistem Informasi Universitas Dinamika, 2022)
RSUD Dr. Soetomo Surabaya is one of the government-owned agencies engaged in health and providing health services for the community. the solution is to design and build a website-based electronic asset management application at Dr. Soetomo. This application is expected to make it easier for asset management to find asset data and find out whether the asset is damaged or not, make it easier to find assets, reduce data duplication, assist in the distribution of borrowed assets and distribution of issued assets. The results of this application trial can help the asset management section in managing incoming and distributed goods, help in storing data so that data cannot be lost, help in overcoming items that are not identified properly, helping the ICT department to number items so that they are easily identified.